Brazilian metropolises: communication groups’ actions against barbarism in the reoccupation of public spaces - Paiva, Raquel (2019)
This paper aims to discuss situations such as the impossibility of free circulation in the cities, the confining and segregation of the population to peripheral areas, the lack of access to public spaces, and finally the confrontation with police violence as a way to immobilize peripheral neighborhoods, through the basic premise of the need for the real use of the city by its people, and communication as a tool of inclusion and mobilization in public space. Beginning with a brief discussion about racism and conservatism as a structural scenario of the reality of life in Brazil, we present an analysis of the communication model adopted by two Brazilian groups in the current context of public spaces’ precariousness: the Papo Reto group (Rio de Janeiro, Southest) and the Tela Firme group (Pará, North). These groups share their discourse production from the peripheral areas of great urban centers, as well as the questioning of how cities have been occupied from the violence, dwelling and culture points of view. The purpose of this paper is to draw a spirit of citizenship inspired by the collectivist notion of polis and commonwealth, as a substitute to a particularistic and conservative vision of the city. We believe that these groups promote ways of urban occupation based on the will to build a more humanized and equal city which includes all kinds of affections and struggles of everyday life.